Abstract and concrete repetitive thinking modes in alcohol-dependence. Issue 4 (1st October 2016) - Grynberg, Delphine; de Timary, Philippe; Philippot, Pierre; D'Hondt, Fabien; Briane, Yasmine; Devynck, Faustine; Douilliez, Céline; Billieux, Joël; Heeren, Alexandre; Maurage, Pierre
ABSTRACT: Emotional and interpersonal deficits play a crucial role in alcohol-related disorders as they predict alcohol consumption and relapse. Recent models of emotion regulation in psychopathology postulate that these deficits are centrally related to increased abstract/analytic repetitive thinking, combined with reduced concrete/experiential repetitive thinking. As this assumption has not been tested in addictions, this study aimed at investigating repetitive thinking modes in a large sample of alcohol-dependent individuals. One hundred recently detoxified alcohol-dependent individuals (29 females; mean age = 49.51-years-old) recruited during the 3rd week of their treatment in a detoxification center were compared to 100 healthy controls (29 females; mean age = 48.51-years-old) recruited in the experimenters' social network, matched at the group level for age, gender, and educational level. All participants completed the Mini Cambridge Exeter Repetitive Thought Scale measuring abstract/analytic and concrete/experiential repetitive thinking modes as well as complementary psychopathological measures (Beck Depression Inventory and State/Trait Anxiety Inventory). Alcohol-dependent individuals have similar levels of concrete repetitive thinking as controls but report significantly higher levels of abstract repetitive thinking ( p < 0.001; d = 1.28). This effect remains significant after controlling for depression and anxiety. Relative to healthy controls, alcohol-dependent patients report more frequent use of abstract/analytic repetitive thinking, with preserved concrete/experiential thinking. Despite the cross-sectional nature of the study, the frequent use of abstract repetitive thinking thus appears to constitute a main feature of alcohol-dependence.